ФАРҒОНА СОМОНИЙ ВОЛИЙЛАР БОШҚАРУВИ ДАВРИДА (Scientific journal of the Fergana State University, 2023)
Based on historical sources and literature, the article for the first time describes the activities of the governors of Ferghana from the Samanid dynasty: Ahmad ibn Asad, Abul Asjos Asad ibn Asad, Ishaq ibn Ahmad, Muhammad ibn Ishaq and Muhammad ibn Asad. The political situation in the Ferghana Valley on the eve of the establishment of the domination of the Samanids here, the events of 823 and 828, the conflict between Nasr and Ismail, some uprisings at the beginning of the 10th century, which led to the withdrawal of Ferghana from the Samanid state are also studied